2011
DOI: 10.1039/c1cp20874h
|View full text |Cite
|
Sign up to set email alerts
|

The phase (trans)formation and physical state of a model drug in mesoscopic confinement

Abstract: Compounds embedded into mesoporous or even microporous matrices are interesting for many emerging applications, such as novel catalysts, sensors, batteries, hydrogen storage materials or modern drug delivery devices. We report on two unexpected phenomena regarding the structural and dynamic properties of a model drug substance (indomethacin) when confined in mesoscopic matrices. Firstly, we show that the confinement directs the crystallization of the drug into a stable polymorph that is not otherwise formed at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
30
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 30 publications
4
30
0
Order By: Relevance
“…The advanced solid-state NMR methods focused on detailed analysis of hydrogen bonding patterns and intramolecular distances and were supported by first principles calculations. 28,38,43,46,51 We report for the first time solid-state NMR spectra of IMC methanol solvate and form V. Due to the fact that IMC form V is formed via desolvation of the IMC methanol solvate, we focus on the changes in the peak positions and intensities for both forms and compare them to the previously assigned peaks of the spectrum of g-IMC (Fig. 2).…”
Section: Resultsmentioning
confidence: 98%
“…The advanced solid-state NMR methods focused on detailed analysis of hydrogen bonding patterns and intramolecular distances and were supported by first principles calculations. 28,38,43,46,51 We report for the first time solid-state NMR spectra of IMC methanol solvate and form V. Due to the fact that IMC form V is formed via desolvation of the IMC methanol solvate, we focus on the changes in the peak positions and intensities for both forms and compare them to the previously assigned peaks of the spectrum of g-IMC (Fig. 2).…”
Section: Resultsmentioning
confidence: 98%
“…As the crystallization of the drug inside the pores requires high loading concentrations [31] and the solubility of IMC in conventional solvents is low, dimethyl sulfoxide (DMSO, purity ≥ 99.5 %, Merck) was used as a solvent. Other studied organic solvents were ethanol (Altia, purity > 99.5 %), acetone (Merck, purity > 99.8 %), and ethyl acetate (Merck, purity > 99.5 %).…”
Section: Chemicals and Measurementsmentioning
confidence: 99%
“…Crystallization inside the pores may occur only if the pore radius is wider than the d-layer. The dependence of crystallinity on pore size has been demonstrated experimentally [19][20]. It has, moreover, been shown that the phase transformations of confined API may differ from those of bulk API because of interactions between the API molecules and the pore walls [20][21].…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…It should be noticed that in the standard calculations it is not possible to take into consideration the dynamics effects resulting from the thermal motions, therefore geometry optimization brings the structure closer to the DFT minimum at 0 K. The common approach is optimization of solely hydrogen atoms positions since in many cases it was found to provide the most accurate results . The calculations are usually performed using the Perdew–Burke–Ernzerhof (PBE) exchange–correlation functional, defined within the generalized gradient approximation (GGA) with the Tkatchenko and Scheffler method for the dispersion (DFT‐TS) correction …”
Section: Introductionmentioning
confidence: 99%